From ice to neurons: investigating the neuroprotective effects of Antarctic microalgae Chlorella variabilis and Chlorella pyrenoidosa extracts - Inan, Benan; Mutlu, Betul; Cakir, Rabia; Balkanli, Didem (SPRINGER HEIDELBERG, 2024)
In this study, it was aimed to examine the neuroprotective effects of ethanolic extracts of Chlorella variabilis YTU.ANTARCTIC.001 and Chlorella pyrenoidosa OZCIMEN.001 microalgae that were isolated from Antarctica in a H2O2-induced oxidative stress model using SH-SY5Y cell line. In this context, first, Antarctic microalgae were cultivated and characterized. It was determined that C. pyrenoidosa and C. variabilis had specific growth rates of 0.093 and 0.097 day(-1), respectively, and doubled their cell concentration in 7 days. With the antioxidant and phenolic content analysis, it was found that 1 mg/mL C. pyrenoidosa and C. variabilis ethanolic extracts had 33-37% radical scavenging activity and 102-107 mg GAE/mg extract phenolic content, respectively. Then, the cytotoxic effects of the microalgae extracts on SH-SY5Y cells were assessed across a concentration range of 6.25-125 mu g/mL. The results indicated a concentration-dependent effect on cell viability, with no observed cytotoxicity within the tested range. Notably, the highest neuroprotective activity was recorded with C. variabilis extract at a concentration of 75 mu g/mL, which maintained cell viability at 73.7% +/- 0.3. These findings showed the significant neuroprotective potential of C. pyrenoidosa and C. variabilis ethanolic extracts, attributed to their substantial antioxidant properties and non-cytotoxic nature at effective concentrations. The promising neuroprotective efficacy of these extracts highlights their potential for therapeutic applications in neurodegenerative disease prevention and treatment.
Keywords: Antarctic microalgae; Chlorella variabilis; Chlorella pyrenoidosa; Neuroprotection; Marine biotechnology; Bioactives; ANTIOXIDANT ACTIVITY; OXIDATIVE STRESS; IN-VITRO; CAROTENOIDS; TEMPERATURE; MANAGEMENT; DISEASE; GROWTH; CELLS; OIL; Biotechnology & Applied Microbiology